A educação enquanto direito público subjetivo: leituras acerca da herança de um direito em diferentes cenários paradigmáticos - Moura, Regiani Rolim de (2019)
Education in Brazil has undergone numerous modifications throughout its history. With Independence (1822) and the proclamation of the National Constitutions, through the thick and thin, Brazilian public education became a right.To better understand this constitutional line that allowed education to be a subjective public right, the following research presents three paradigmatic scenarios of Brazilian post-independence education: education as a privilege; education as a right followed by compulsory education; and education as a subjective public right. Debating about these scenarios, this research problematizes the right to education as an inheritance of the treasures of human civilization, and therefore it is not appropriate that someone can not inherit them. Based on this assumption and considering the perceptions, as well as the unfamiliarity of this right demonstrated by parents, students, professionals of education and educational institutions, this research tries to answer the following questions: " what's the meaning of education as a subjective public right and how can we perceive in practice the experience of this right? ". Responding this question, following the general aim of the investigation to "understand what education is as a subjective public right, identifying concrete cases of applicability of this right," this study analyzes 13 cases concerning subjective public right in education passed by the Court of Justice of Santa Catarina in the period from 2008 to 2018, trying to understand how this right is characterized in the sphere of the judiciary, as well as his possible forms of use. Guided by the methodology based on Content Analysis proposed by Laurence Bardin, this study looks for the Constitutions and to documents such as the Statute of the Child and Adolescent, the Law of Guidelines and Bases and the National Plan of Education, in addition to redeeming ideas and conceptions of different authors on Education and Law. Based on this theoretical body, it interprets concrete cases of use of the subjective public right to the education. It can be stated that the main results of this investigative process is the conviction about the need of deepening understandings about the status of education as a public right subjective.